Orientalisme, Liberalisme Islam, Dan Pengembangan Studi Islam Di IAIN - Ahwan Fanani (Universitas Islam Negeri Mataram, 2007)
The recent development of Islamic Studies in IAIN (The State Institute for Islamic Studies) shows a trend to combine Islamic studies based on traditional approaches and methods with that employed in Western universities or orientalism. The trend is promoted by Indonesian scholar graduates from Western Universities, and results in the growth of Islamic liberalism. To some Islamic revivalism advocates, the trend is considered misleading, and IAIN with its lecturers pursuing studies in Western universities are accused to be agents of Islamic liberalism in Indonesia. Contrarily, some Islamic scholars see the trend as a bright future for development of Islamic studies in Indonesia. The situation puts IAIN in a dilemma either to keep on traditional approaches and methods or to adopt deliberately new ones coming from Western tradition. In my opinion, IAIN should apply them both and combine them to promote better future of Islamic studies in Indonesia.